Dengue Fever a Resilient Threat in the Face of Innovation - Abelardo Falcón-Lezama, Jorge; Betancourt-Cravioto, Miguel; Tapia-Conyer, Roberto (IntechOpen, 2019)
For over 70 years, dengue fever has challenged health systems in every region of the World. It has evolved from a benign febrile illness from the tropics to a major concern in urban settlements, overwhelming health infrastructure with large outbreaks, as it continues to teach us important lessons with its complexities. This book intends to review the latest updates on dengue fever, the tools available for its study and control, and promising technologies currently in the pipeline. With this work, the editors wish to provide students with an updated reference text on the basics of this disease as well as researchers and academics, with a useful document to understand the current outlook and the perspectives for the future.